El acto educativo en el marco de la pandemia, un ejercicio comparativo entre dos instituciones educativas de bogotá (Memorias Sifored - Encuentros Educación UAN, 2021)
Within the framework of the response to the global contingency due to Covid -19, a comparative exercise is proposed based on the observation of two experiences in educational institutions in Bogotá about the way in which the educational act is developed, following three categories: use of ICTs, student participation and presentation of content in the digitally assisted classroom. Based on these, guiding questions were prepared for the collection process (observation of three videos from each institution), description and analysis of information.Among the main findings, the creativity and resourcefulness of teachers and students is highlighted to develop in the best way the classes assisted by technology, using basic tools for communication, interaction and action, in the midst of the scarce installed capacity. In this sense, the participation of students, which can be classified as active, could be enhanced through the use of free, restricted and institutional ICTs. In those that have to do with the presentation of content, the most relevant device is the voice (oral presentation of the teacher) sometimes supported by Microsoft Word and Slideshare presentations. In accordance with the foregoing, the commendable work and adaptability of teachers and the importance of qualification and installation of capacity at the institutional level are shared as conclusions to continue offering quality education.